Egypt : Gulf of Aqaba Environmental Action Plan - World Bank; European Union (World Bank, Washington, DC, 2013)
The intensive development of tourism in the Gulf of Aqaba presents both an opportunity and a dilemma for Egypt. Intensive tourism, if left unmanaged, can inflict irreversible damage on coral reef and desert ecosystems and curtail the area's economic potential. Together with current projections for a rapid expansion of the tourism base in the Aqaba coast, degradation from mounting recreational activities give rise to serious concerns about the sustainability of tourism development in the region. The challenge is to plan for economic development within a sound environmental framework. Implementing the Gulf Of Aqaba Environmental Action Plan (GAEAP) would protect marine resources, including coral reefs and fisheries, and conserve the aesthetic attributes of the Gulf environment and waters upon which the tourist industry depends. This action plan comprises activities in nine categories: institutional strengthening, enforcement of legal and regulatory framework at the South Sinai Governorate level, management of marine pollution, flood and earthquake protection, water and wastewater management, solid waste management, protected areas management, public awareness and environmental education, and assures sustainability of environmental protection in the Gulf of Aqaba. The highest priority actions are decentralizing the institutions to have a presence on the ground, and enforcing the legal and regulatory framework for implementing curative and preventive environmental measures.